KEMAMPUAN MENULIS PANTUN DENGAN MODEL PEMBELAJARAN QUANTUM TEACHING PADA SISWA KELAS VII.C SMP NEGERI 16 KOTA JAMBI TAHUN AJARAN 2014/2015 - Gafar, Abdoel (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
Pantun is an Indonesian Malay literature consisting of four lines. The first and second rows are sampiran, third and fourth lines are the contents, as well as ab-ab rhyming. This research aims to describe the ability to write rhymes with quantum learning model of teaching in Class VII.C Junior High School 16 Jambi City School Year 2014/2015. The method used in this research is descriptive qualitative approach method. The results of this research is to show based on the systematic aspects of writing, use of language, and clarity of the contents, obtained an average value of 84, so the conclution of the ability students to write rhymes are very good. Keywords : writing, pantun, quantum